Germination characteristics of five coexisting neotropical species of Acacia in seasonally dry Chaco forests in Argentina - Venier, Maria Paula; Cabido, Marcelo Ruben; Funes, Guillermo (Wiley, 2019)
At a regional scale, habitat heterogeneity can play a very important role in allowing the coexistence of species through their specialization in the use of patches differing in environmental conditions. Here, we explore responses of seed germination to environmental and anthropogenic factors of five Acacia species that co‐occur in subtropical dry Chaco forests in central Argentina and the habitat heterogeneity of this region. Open and closed sites were characterized in terms of environmental factors by measuring temperature, water content, light quality and soil conditions. Through germination experiments, we evaluated seed responses to both environmental (temperature, light quality and water stress) and anthropogenic factors (fire and cattle). Data were analyzed through a univariate analysis (generalized linear model, GLM) followed by a multivariate analysis (principal component analysis, PCA) in order to obtain a general pattern of Acacia seed responses. Some differences were detected among the Acacia species at the species level and the multivariate analysis (PCA) showed a general pattern with two groups of species differing in germination characteristics: A. aroma, A. caven and A. atramentaria had a higher number of hard seeds after fire and seed consumption by cattle, whereas A. praecox and A. gilliesii showed a reduced time to germinate under different environmental conditions. The multivariate analysis suggests a regenerative niche differentiation between two groups of Acacia species. The habitat heterogeneity described in the dry Chaco forests from central Argentina could facilitate the coexistence of the five Acacia species at the landscape and regional levels.